Public advisory services for early-stage companies in northern sparsely populated area - Leviakangas, Pekka; Saarela, M.; Kauppila, O.; Niinikoski, E.; Muhos, M. (2015)
In developed countries, the public sector allocates substantial resources to support entrepreneurship. Current literature provides limited evidence on how public advisory services should be efficiently and effectively organised. This study investigated what the perceived significance and service level of public advisory services is. A single case study focusing on a sparsely populated region in Northern Finland was performed by carrying out orientation interviews and a customer survey. As a result of this study, the levels of successfulness and the importance of the public advisory services were clarified from the customers' perspective. The results imply that the services are particularly important in the very beginning of the development of the business. It is also then when the most tailoring is called for. This research includes a novel sample, reflecting experiences particularly from a northern sparsely populated area. The perceived customer value of the services is a significant new viewpoint.